Bacteriophages as a Biocontrol Strategy to Prevent the Contamination of Meat Products with Escherichia coli – a Meta-Analysis - VEGA IRACEMA ISLAS; RODRÍGUEZ NYDIA EDITH REYES; PÉREZ VICTOR JOHAN ACOSTA; VELÁZQUEZ ANDREA PALOMA ZEPEDA; SÁNCHEZ VICENTE VEGA; ARANA JORGE LUIS DE LA ROSA; NOGUEZ JESÚS BENJAMÍN PONCE; GÓMEZ DE ANDA FABÍAN RICARDO (Polish Journal of Microbiology)
Bacteriophage-based biocontrol is a cost-effective, sustainable strategy with low ecological impact, which can control the growth of bacteria such as Escherichia coli that impacts public health problems. This work aimed to perform a meta-analysis to evaluate the implementation of bacteriophages as a biocontrol strategy to prevent the contamination of meat products with E. coli. The search was performed by two field experts to avoid reviewer bias. The initial search identified 2,695 bibliographic sources, of which 2,480 were discarded because they did not meet the inclusion criteria, which were the origin of phage, application method, phage taxonomy, E. coli pathotype and meat products, getting 157 articles because they were duplicates, and 47 because they lacked the necessary numerical data. Finally, 11 articles were selected for quantitative analysis. Likewise, phage characteristics (p < 0.05) and E. coli pathotype (p < 0.05), showed that the bacteriophage-bacteria ratio is an item that should be taken into account for the design of bacteriophage application strategies. This meta-analysis evaluates the use of phages in the reduction of E. coli in meat products, considering multiple methodological criteria. Studies were included that specify the origin of the phages (natural or modified), their method of application (direct in meat, in solution, in aerosol, etc.), their taxonomic classification, as well as the pathotype of the target E. coli (EHEC, ETEC, etc.). In addition, the different types of meat products were analyzed, including beef, pork, and chicken. These criteria help clarify the factors affecting phage therapy efficacy in the meat industry.